Classify Aggregate In Asphalt Pavement Layers (A.C-B.C) using Sieve Shaker - Mochamad Rizki; Agata Iwan Candra; Evita Fitrianis Hidiyati; Dikhy Ridho Laksono; Ramadhan Mahendra; Muhammad Lutfi Amzari; Mukhammad Ibnul Mubarok; Muhammad Feggi Saputra (LPPM of NAROTAMA UNIVERSITY, 2022)
Aggregates are a significant feature of asphalt mixtures, which significantly affect the volumetric properties and mechanical performance. Layers of concrete asphalt consist of a mixture of fine aggregates, coarse aggregates, and fillers mixed with penetration grade asphalt. The concrete pavement layer (asphalt concrete) has several types: wear surface layer, intermediate surface layer, and foundation layer. The experimental research method with the gradation testing method using the Sieve Shaker machine with aggregate objects. The aggregate used in the form of fine aggregates from Lumajang sand and coarse aggregates from Kediri Kediri is taken randomly with a maximum size of 2.36 mm, aggregate used in the form of corals originating from Kedak area, Semen Subdistrict, Kediri Regency with a maximum size of 19mm. This study aimed to determine the feasibility of aggregate classification in the classification of road pavement layers. The study was conducted using the Sieve Shaker machine with reference to the AASHTO T27. This study obtained the results that the aggregates tested from the Kedak, Kediri, and Pasir Lumajang regions deserved to be included in the Asphalt concrete A.C-B.C category in accordance with Bina Marga Division 6.